Hisab Awal Bulan Syiah Kuala (Menyunting Dari Naskah Risalah Asy-Syaikh ‘Abd ArRauf Fi At-Taqwim) - Cosara, Wali (Universitas Islam Negeri Mataram, 2022)
Treatise of Asy-Shaykh Abdur Ar-Rauf fi At-Taqwim's is one of the collections of the Pedir Museum in Aceh which consists of three sheets (six pages) in Arabic-Malay language which discusses the calculation of the Hijri calendar. However, the text does not explain the origin of the numbers and their formulas. So the calculation of the Hijri calendar described in the manuscript cannot be used at this time because the difference is very far from the Hijri calendar that we usually use. This research is included in library research, namely research by collecting data and information from books, journals, and other recorded documents related to the calculations described in the text of As-Shaykh 'Abdur Ar-Rauf fi At-Taqwim's Treatise. Data analysis was carried out by examining the origin of the letters of the year and the letters of the month and their corrections so that the calculation of the beginning of the Hijri month described in the AsShaykh 'Abdur Ar-Rauf fi At-Taqwim treatise can be used throughout the ages. In this study there is a synthesis that the calculation of the beginning of the month described in the As-Shaykh 'Abdur Ar-Rauf fi AtTaqwim treatise must be corrected to adjust to the hijri calendar that we use every day.Keywords: Treatise of As-Shaykh 'Abdur Ar-Rauf fi At-Taqwim, Early Months, Syiah Kuala.